OPTIMALISASI PATROLI KENDARAAN RODA 4 SAT SAMAPTA POLRES SRAGEN GUNA MENCEGAH CURANMOR DALAM RANGKA MENDUKUNG POLRI YANG PRESISI - MUHAMMAD RIZKY FEBRIANTO NASRI (Indonesian Journal of Police Studies, 2022)
In the final project entitled Optimizing 4-wheeled vehicle patrols at the Sragen Police to prevent the crime of motor vehicle theft in order to support the Indonesian National Police make a predictive, responsibility, and transparency justice (Presisi), it discusses issues related to the implementation of 4-wheeled vehicle patrols at the Sragen Police and the optimization of 4-wheeled vehicle patrols by the Sat Samapta Polres Sragen. The background of writing this final project is that there is still a criminal act of motor vehicle theft in Sragen Regency so it needs to be prevented through police action, including patrol activities. However, it turns out that the patrol activities of 4-wheeled motorized vehicles by Sat Samapta are still not optimal because there are several problems in aspects of personnel, budget, facilities, machines and society. The purpose of this final project is to find out the efforts carried out for optimizing the 4-wheeled patrol of the Sat Samapta Polres Sragen in order to prevent the crime of motor vehicle theft in order to support the Precise Police. The research method used in this final project is a qualitative research method with data analysis techniques using an interactive model, namely: collecting data, reducing data, presenting data, and drawing conclusions. While the theoretical basis used in this final project is the management theory and the management theory of the police. The results obtained from the research that has been carried out, it is known that in order to optimize the patrol of Sat Samapta 4-wheeled motorized vehicles, Sat Samapta Polres Sragen in order to prevent theft of motorized vehicles in order to support the Precise Police, namely by making improvements to aspects of patrol personnel, making effective use of the available budget. , caring for and maintaining supporting facilities and machines, especially cars and increasing cooperation with various parties such as the community and other agencies, namely Sragen Regency Government and Kodim 0725 Sragen. Keywords: Patrol; Samapta; Robbery; INP Presisi